2018
DOI: 10.1136/bmjoq-2018-000400
|View full text |Cite
|
Sign up to set email alerts
|

Faecal immunochemical testing implementation to increase colorectal cancer screening in primary care

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death in USA, and CRC screening remains suboptimal. The aim of this quality improvement was to increase CRC screening in the internal medicine clinic (IMC) patients, between the ages of 50–75 years, from a baseline rate of 50%–70% over 12 months with the introduction of faecal immunochemical test (FIT) testing. We used the Plan–Do–Study–Act (PDSA) method and performed a root cause analysis to identify barriers to acceptance of CRC screening. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…29,30 Intervening on this population is challenging but supported by a Cochrane Review, guaiac fecal immunochemical test (FIT) can reduce colorectal mortality by 15%, and providing appropriately chosen patients with home use FIT tests through primary care has improved screening rates, sustaining a screening rate of 75%. 31,32 Currently screening routinely for cancer does not occur in the emergency setting, but for many vulnerable patients (uninsured, lower SES, racial minorities), the emergency room serves as the only opportunity for routine care and we should begin to explore alternative strategies to maximally improve the care of these patients. 33 Removing the barriers to cancer screening, such as providing patients with FIT cards prior to discharge may represent an opportunity to increase adherence to CRC screening and reduce the burden of emergently diagnosed CRC.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Intervening on this population is challenging but supported by a Cochrane Review, guaiac fecal immunochemical test (FIT) can reduce colorectal mortality by 15%, and providing appropriately chosen patients with home use FIT tests through primary care has improved screening rates, sustaining a screening rate of 75%. 31,32 Currently screening routinely for cancer does not occur in the emergency setting, but for many vulnerable patients (uninsured, lower SES, racial minorities), the emergency room serves as the only opportunity for routine care and we should begin to explore alternative strategies to maximally improve the care of these patients. 33 Removing the barriers to cancer screening, such as providing patients with FIT cards prior to discharge may represent an opportunity to increase adherence to CRC screening and reduce the burden of emergently diagnosed CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Some team-based primary care interventions have improved colorectal cancer screening rates using innovative strategies, including the use of community health worker outreach and the introduction of fecal immunochemical tests; however, these practices had lower baseline rates than AIC practices, which exceeded the national average among commercially insured patients in 2013 (approximately 60%). 48 - 50 There is mixed evidence on the association between breast cancer screening rates and team-based care: 1 study reported significant improvements of 3.5 percentage points over 3 years in practices with care teams, while another found no significant changes. 51 , 52 Fewer studies have examined changes in cervical cancer screening rates associated with adoption of team-based care, though 1 found no significant differences among army primary care patients following the formation of care teams.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the entry age for CRC screening has recently been lowered to include those aged 45 years and older, and while alternatives such as the fecal immunochemical test (FIT) are becoming increasingly popular, it is reasonable to suspect that there will be larger demand for surveillance colonoscopies compared to screening colonoscopies in the near future [18][19]. In light of this, we should anticipate a larger volume of surveillance procedures and establish appropriate benchmarks to ensure quality surveillance colonoscopy performance and to improve detection rates of interval CRC.…”
Section: Discussionmentioning
confidence: 99%